Az Északnyugat-Dunántúl humán erőforrásai - Csapó, Tamás (Tér és Társadalom, 1997)
The study is part of the analysis of the long term regional development concept of Northwest Transdanubia and aims to explore and demonstrate out of the endogenous resources the situation of human capital on which a development strategy can be built. The essay covers the changes in the number of population and its composition, the structure of the population by sex, age and ethnic belonging and especially by school education and language skills. Finally, it explores economic activity and employment structure. The major findings are as follows: Human resources in Northwest Transdanubia are more favourable than the national average, providing a good basis for the developments; the qualification of the population in the region is favourable, many speak German language, the economic activity is high and the employment structure is of an urban type, unemployment rate is low and the health care and social conditions of the population are more favourable than the national average; however, the ageing of the population and the low rate of births and natural increase are a problem, as is the lack of language skills of the population, aside from German language; on the whole, the trends are favourable with regard to human resources, in connection with the increased appreciation of the region; the differences within the region are extremely large, exceeding the national average, between the small regions, also villages and towns, and villages of different size.